Adsorpsi Hg(II) Menggunakan Sargassum crassifolium dengan Adanya Pb(II), Cu(II) dan Fe(II) - Nurhadini, Nurhadini; Silalahi, Imelda H. (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2017)
Amalgamation use mercury in mining process especially small-scale gold mining and it has been impacted on mercury contamination in environment. Mercury is one of heavy metal that toxic and can accumulate in water, soil and organism. Adsorption method is one of alternative option that effective to remove heavy metal. This method depends on adsorbent type, pH, adsorbent composition with metal or presence of several metal ions. Beside mercury, wastewater of mining gold have another metal ions such as Pb(II), Cu(II) dan Fe(II) can be found by human activity or naturally present. This research aim is to study effect of Pb(II), Cu(II), and Fe(II) in Hg(II) adsorption by using Sargassum crassofolium adsorbent. Research stages are adsorbent activation and mercury adsorption on binary and ternary system respectively in equimass amount of metals ion and equimolar amounts of metals. Based on adsorption analysis is known that Pb(II) and Cu(II) is Hg(II) competitor while Fe (II) is not Hg(II) competitor in adsoption by using Sargassum crassifolium. On binary system in equimass amount of metals ion and equimolar amounts of metals that the largest decreasing effect of Hg(II) adsorption in system contain Cu(II).